Comparison and Analysis of Twist Pitch Length Test Methods for ITER Nb3Sn and NbTi Strands. Issue 9 (September 2015) - Fang, Liu; Feng, Long; Huixian, Gao; Chao, Chen; Bo, Liu; Yu, Wu; Huajun, Liu
Abstract: A twisted multifilamentary structure is needed for Nb3 Sn and NbTi strands to be used in the International Thermonuclear Experimental Reactor (ITER) magnets. The Cable-In-Conduit Conductor (CICC) for the coils of ITER relies on twisted, multifilament, Nb3 Sn and NbTi based composite strands. As important parameters for the superconducting strand design and production, the twist pitch length and the direction of strands must meet the requirements according to ITER Procurement Arrangement (PA) and this must be verified. The technical requirements include 15 mm ± 2 mm for twist pitch length and right hand twist for direction. The twist pitch and the twist direction can be measured on straight sections of strand, which is recognized by the repetition of filament bundles or by the angle of the filaments. Several test methods and results were described and compared in the present paper. The accuracy, the uncertainty and the feasibility of different methods were analyzed and recommended measurement methods were proposed for ITER strands verification.